2012
DOI: 10.5402/2012/589817
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Followup: A Major Challenge to Successful Implementation of Prevention of Mother-to-Child Transmission of HIV-1 Programs in Sub-Saharan Africa

Abstract: Purpose. The purpose of this paper was to explore how loss to followup (LFTU) has affected the successful implementation of prevention of mother to child transmission of HIV-1 (PMTCT) programs in sub-Saharan Africa. Methods. We conducted an electronic search from the following databases PubMed, ScienceDirect, Directory of Open Access Journals (DOAJs), and PyscINFO. Additional searches were made in WHO, UNAIDS, UNICEF, Google, and Google scholar websites for (1) peer-reviewed published research, (2) scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 51 publications
11
64
0
Order By: Relevance
“…This was attributed to the fear of domestic violence after disclosing their status to their spouses. Some quantitative studies have shown this to be true [18].…”
Section: Advances In Public Healthmentioning
confidence: 99%
“…This was attributed to the fear of domestic violence after disclosing their status to their spouses. Some quantitative studies have shown this to be true [18].…”
Section: Advances In Public Healthmentioning
confidence: 99%
“…Additionally in children <5 years, severe immunodeficiency was documented in 56–64 % of children initiating antiretroviral therapy in resource-limited settings compared with 22 % in the USA (Koller et al 2015). Apart from late treatment initiation, retention of HIV-exposed children in care is low, with high loss to follow-up (19–89 %) at various points in the diagnostic and treatment cascade (Kalembo and Zgambo 2012). In India 63 % of HIV exposed infants were lost to follow-up after 1 year (Kumar et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…non-disclosure of HIV positive status and weak systems for social support resulting in poor retention in care and low adherence to treatment : Reasons for loss to follow-up are protean but included fear, stigma, home deliveries, low socio-economic status and lack of transport to access health facilities (Kalembo and Zgambo 2012). Non-disclosure of HIV positive status has also been associated with poor adherence (O’Malley et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…While the rates of uptake of tasks to PMTCT are known, it is difficult to estimate how many new MLH transition to HIV care post birth. In trials evaluating PMTCT the loss to follow-up ranges from 19% to 89% [5]. Loss to follow-up among adults in Johannesburg indicate that 30% are disengaged from care by 12 months [6].…”
mentioning
confidence: 99%